Geomorphological dynamics of river banks: assessment of changes due to erosion-accretion processes of Marikina River - Avila, Camille Cassandra A.; Madonna P. Danao (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
This thesis examines the geomorphological dynamics of the Marikina River’s banks from 2004 to 2024, focusing on how erosion and accretion processes have reshaped the river's morphology across natural, agricultural, and urban landscapes. Using satellite imagery, time-series mapping, field observations, and an adapted Multi-Criteria Decision Analysis (MCDA), the study evaluates how environmental factors such as slope, soil type, land use, vegetation cover, and flood susceptibility interact to influence riverbank change. A total of 77 river edge profiles were assessed to identify zones susceptible to bank movement and classify them under management categories: Preservation, Conservation Needed, Improvement Required, or Creation. The results show that agricultural areas experienced the most dynamic shifts, natural areas showed moderate changes, and urban zones remained relatively stable due to engineered protections. Most profiles were rated as requiring conservation or improvement, with none qualifying for preservation or creation. These findings highlight that riverbank behavior is shaped not by isolated factors but by their combined effects, emphasizing the need for site-specific, adaptive management approaches. The study suggests practical, landscape-based strategies to enhance riverbank stability and resilience, contributing to informed river corridor planning and sustainable land-use policy.
Include appendices
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman
Keywords: Geomorphological mapping -- Marikina; Marikina River; Riparian areas -- Erosion -- Marikina; Landscapes -- Management; Riparian areas -- Stability